Progressive multiple sclerosis: latest therapeutic developments and future directions - Simon Faissner; Ralf Gold (Therapeutic Advances in Neurological Disorders, 2019)
Multiple sclerosis (MS) is a chronic inflammatory condition of the central nervous system leading to demyelination and neurodegeneration. While the initial presentation is mostly characterized by a relapsing–remitting disease, patients often progress naturally after 10–15 years to a secondary-progressive disease course. Another 10–15% present with an initial, primary-progressive MS course. Pathogenic mechanisms possibly driving progression include continued compartmentalized inflammation by T- and B-lymphocytes and cells of innate immunity, oxidative stress, iron accumulation, and consecutive mitochondrial damage, altogether leading to neurodegeneration with accumulation of disability. Increasing knowledge about pathogenic mechanisms involved in progressive MS helps to design more specific and precise therapeutic approaches. Successful examples are the B-cell targeting monoclonal antibody ocrelizumab, effective in primary progressive MS, and the sphingosine-1-receptor modulator siponimod, effective in active forms of secondary-progressive MS. Apart from that, other medications such as the B-cell targeted antibody ofatumumab, cladribine due to T- and B-cell depletion, and other sphingosine-1-receptor modulators such as ozanimod and ponesimod are under development. Moreover, some therapeutic approaches in preclinical stages are under development. In this review, we will summarize the newest therapeutic development in the field of progressive MS of the last 3 years, and shed light on auspicious substances with similar mechanisms and new developments in the therapeutic pipeline, presumably supporting a bright future for progressive MS treatment.